Variation in the Quality of Life within Punjab: Evidence from MICS, 2007-08 (The Pakistan Development Review, 2010)
Since quality of life research is essentially concerned with measuring and monitoring welfare. In order to measure quality of life, one must have a theory of what makes up a good life [Cobb (2000)]. There is a variety of such theories and notions of what constitutes a ‗good life‘ and correspondingly different concepts of welfare and quality of life have been developed. Various approaches and operationalisations are to be distinguished, each of which reveals a different concept of welfare and thus highlights different components and dimensions [Noll (2000)]. Among the various efforts to operationalise welfare in general and the quality of life concept in particular, two contrary approaches are to be distinguished, which define the two extreme positions on a broad continuum of concepts currently available: the Scandinavian level of living approach [Erickson (1993)] and the American quality of life approach [Campbell (1976)]. The Scandinavian approach focuses almost exclusively on resources and objective living conditions, whereas the American approach emphasises the subjective well-being of individuals as a final outcome of conditions and processes.